Labelled loans and human capital investments - Britta Augsburg; Bet Caeyers; Sara Giunti; Bansi Malde; Susanna Smets (Institute for Fiscal Studies (IFS), 2021)
Imperfect capital markets and commitment problems impede lumpy human capital investments. Labelled loans can alleviate both constraints, but little is known about their effectiveness in practice. We draw on a cluster randomized controlled trial in rural India to provide the first evidence that labelled microcredit is effective in increasing take-up of a lumpy human capital investment, a safe toilet. Testing predictions from a theoretical model provides novel evidence that loan labels influence household borrowing and investment decisions. Not all loans are used for sanitation investments, suggesting that loan labels offer a soft commitment incentive.
Keywords: O16; D14; G41; I12; 330